A Clonal Lineage of VanA-Type Enterococcus faecalis Predominates in Vancomycin-Resistant Enterococci Isolated in New Zealand - Manson, Janet M. (American Society for Microbiology, 2003)
Avoparcin was used as a feed additive in New Zealand broiler production from 1977 until June 2000. We report here on the effects of the usage and discontinuation of avoparcin on the prevalence of vancomycin-resistant enterococci (VRE) in broilers. Eighty-two VRE isolates were recovered from poultry fecal samples between 2000 and mid-2001. VRE isolates were only obtained from broiler farms that were using, or had previously used, avoparcin as a dietary supplement. Of these VRE isolates, 73 (89%) were VanA-type Enterococcus faecalis and nine (11%) were VanA-type Enterococcus faecium. All E. faecalis isolates were found to have an identical or closely related pulsed-field gel electrophoresis (PFGE) pattern of SmaI-digested DNA and were susceptible to both ampicillin and gentamicin. The PFGE patterns of the nine E. faecium isolates were heterogeneous. All VRE contained both the vanA and ermB genes, which, regardless of species or PFGE pattern, resided on the same plasmid. Eighty-seven percent of the VRE isolates also harbored the tet(M) gene, while for 63 and 100%, respectively, of these isolates, the avilamycin and bacitracin MICs were high (≥256 μg/ml). Five of eight vancomycin-resistant E. faecalis isolates recovered from humans in New Zealand revealed a PFGE pattern identical or closely related to that of the E. faecalis poultry VRE isolates. Molecular characterization of Tn1546-like elements from the VRE showed that identical transposons were present in isolates from poultry and humans. Based on the findings presented here, a clonal lineage of VanA-type E. faecalis dominates in VRE isolated from poultry and humans in New Zealand.